Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Oyster aquaculture enhances sedimentary nitrogen removal in a subtropical estuary - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Xin Luo; Dost Muhammad; Shahzad Afzal; Ke Pan (Regional Studies in Marine Science, 2026)

The dual role of humic acids in driving anaerobic oxidation of methane in paddy soils - Dehong Yang; Yanping Wang; Yuanhao Lan; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Identification and functional analysis of floral terpene synthase genes in Curcuma alismatifolia - Zihan Cao; Lan Wang; Di Huang; Guilan Wu; Xinyue Li; Yuechong Yue; Yunyi Yu; Rangcai Yu; Yanping Fan (Planta, 2024)

Changes of MRGs and ARGs in Acinetobacter sp. SL-1 used for treatment of Cr(VI)-contaminated wastewater with waste molasses as carbon source - Hui Wu; Rongxiao Wang; Yanping Ma; Tian C. Zhang; Yexing Yu; Jirong Lan; Yaguang Du (Science of The Total Environment, 2024)

Highly Sensitive Detection of PIK3CA Mutations by Looping-Out Probes-Based Melting Curve Analysis - Boheng Xu; Yanping Lan; Danjiao Luo; Yangsi Zheng; Runfang Ni; Guoqiang Su; Qiuying Huang; Qingge Li (Biochemical Genetics, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Auxin and CmAP1 regulate the reproductive development of axillary buds in Chinese chestnut (Castanea mollissima) - Yunhe Cheng; Lili Cheng; Guanglong Hu; Xiaomeng Guo; Yanping Lan (Plant Cell Reports, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

The complete chloroplast genome sequence of Actinidia kolomikta from north China - Yanping Lan; Lili Cheng; Wugang Huang; Qingchang Cao; Zhijun Zhou; Anjin Luo; Guanglong Hu (Conservation Genetics Resources, 2018)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

The complete chloroplast genome sequence of the endangered Chinese endemic tree Corylus fargesii - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Xueqiang Wang; Wugang Huang (Conservation Genetics Resources, 2017)

The complete chloroplast genome sequence of Corylus chinensis Franch - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Wugang Huang (Conservation Genetics Resources, 2017)

Isolation and Characterization of a Novel Virulent Phage of Lactobacillus casei ATCC 393 - Xi Zhang; Yu Lan; Wenchao Jiao; Yijing Li; Lijie Tang; Yanping Jiang; Wen Cui; Xinyuan Qiao (Food and Environmental Virology, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)